Alfabetização em saúde de adolescentes em uso de anticoncepcional hormonal - Tomé, Marcela Ariadne Braga Gomes (2022)
Studies indicate that inappropriate and inconsistent use of contraceptives, combined with beliefs and myths, can contribute to the outcome of pregnancy among sexually active adolescents who make use of these methods. Thus, given this concern, the objective was to evaluate the literacy in the health of adolescents using hormonal contraceptives. A descriptive, cross-sectional, quantitative study conducted with students from the public school system of the city of Fortaleza-CE, Brazil, totaling 147 adolescents, between January and October 2020, in which the socio-demographic and reproductive questionnaire and the Health Literacy Scale (HLS) were used-14. More than half of the adolescents had a high level of health literacy, the critical level presented a higher average than the other domains. The variables significantly associated that increase the chance of adolescents having low literacy were living with their mother (p = 0.024; OR = 4.4), low family income (p = 0.004; OR = 14.2), choosing the method on their own (p = 0.003; OR = 4.1), and having religion (p = 0,008, RC = 4,1). It is necessary to expand this research to a greater number of adolescents and to sensitize health professionals on the theme of health literacy, in order to define better strategies and plans regarding the health of adolescents.